Preschool aged child’s literacy experience through everyday play in the home: A creative pathway to early literacy learning. - Ojo, Nanbam Y.; Ekanem, Inibehe E. (Advances in Social Sciences Research Journal, 2021)
Two major events have brought research on preschool aged children to the centre of educational research in Nigeria. First, Nigeria is a signatory to the United Nations Convention, which is leading a campaign for the adoption and ratification of the Rights of the child. Secondly, the introduction of early childhood education in tertiary teacher training programmes has pointed to the need for quality research in the diverse fields of early childhood studies. One area that is yet to receive enough research attention relates to doing early literacy research in the home, in particular, with preschool aged children in the context of play. Using the empirical context of a six-week study of a 4-year-old preschool child in her home in Jos Plateau State, this paper studies how the child’s engagement in play enriched her early literacy learning. The study adopts participant observation and interview methods to collect data from multiple sources in the child’s home. Theoretically, the study is framed on an eco-cultural approach on child-initiated play and learning with accessible literacy resources. The theoretical framework enabled the identification of the learning opportunities in the home and the child’s capacity to act independently. It was also useful for studying the parents’ ethnotheories and support for learning in the home. Using thematic analysis, the findings indicate the child was critically engaged with hybrid traditions of literacy- texts and representations. The paper has implications for policy on partnering with parents for children’s literacy development.